Influence of Health Education with Audio Visual Media on Anxiety Facing Menarche with Students Elementary Schools 006 Long Iram - Mulyani, Yesi; Lis Arming Gandini, Andi; Adif C, Nino (Rifa'Institute, 2023)
Introduction: Early puberty in girls is one of the best examples of adolescent mental health problems including anxiety. The results of Riskesdas show that based on reports of respondents who have experienced menstruation, the average age of menarche is 13 years (20%) with an earlier occurrence at the age of less than 9 years and some delaying up to 20 years. Objective: To determine the effect of health education with audiovisual media on anxiety facing menarche in students of Elementary Schools 006 Long Iram. Methods: Experimental research design with pre-experimental design one group pretest posttest. Results and Discussion: It was found that before the intervention providing education with audiovisual media, most of them experienced moderate anxiety as many as 21 people (61.8%), after the intervention most of the anxiety became a mild category as many as 21 people (61.8%). A total of 18 people had anxiety after the health education intervention with audio-visual media about menarche decreased compared to before the intervention. Conclusion: There are differences in student anxiety before and after being given health education with audio-visual media about menarche at Sekolah Dasar 006 Long Iram students